The Work of Photography Reimagined: The Soviet Moment in France, 1928–34. Issue 4 (2nd October 2018) - Dell, Simon
Abstract : This article examines the photographic practices of the French Communist Party during the 'Third Period', when the Communist International adopted its most intransigent policies. Through an analysis of the magazines Nos Regards and Regards sur le monde du travail, I show that the Communists adopted a montage technique which expanded the practice from juxtapositions on the page to juxtapositions orchestrated across the whole publication. Photographs were thus used to articulate the conflict between opposed economic and political systems through sustained comparisons of capitalist countries and the 'fatherland of the International proletariat'. In the process, the magazines became collective works rather than miscellanies of individual articles, mounting a direct challenge to the practices of the bourgeois press. This challenge was also extended to the role of the press photographer, which the Communists proposed to supplant through the collaboration of worker photographers. Thus, the very work of photography was to be reimagined.